Disturbed Cerebellar Growth Trajectories in Adolescents Who Initiate Alcohol Drinking - Sullivan, Edith V. (Biol Psychiatry, 2019)
OBJECTIVE: The cerebellum is a target of alcoholism-related brain damage in adults. Yet no study has prospectively tracked deviations from normal cerebellar growth trajectories in adolescents before and after initiating drinking. METHOD: MRI tracked developmental volume trajectories of 10 cerebellar lobule and vermis tissue constituents in 548 no-to-low drinking youth age 12-21 years at induction into this five-site, National Consortium on Alcohol and NeuroDevelopment in Adolescence (NCANDA) study. Over the 3-4 year longitudinal examination yielding 2043 MRIs, 328 youth remained no/low drinkers while 220 initiated substantial drinking after initial neuroimaging. RESULTS: Normal growth trajectories derived from no/low drinkers indicated that gray matter volumes of lobules V-VI, Crus II, VIIB, and X declined faster with age in male than female youth, whereas white matter volumes in Crus I-II and lobules VIIIA-VIIIB expanded faster in female than male youth; CSF volume expanded faster in most cerebellar regions of male than female youth. Drinkers exhibited accelerated gray matter decline in anterior lobules and vermis, accelerated vermian white matter expansion, and accelerated CSF volumes expansion of anterior lobules relative to youth who remained no/low drinkers. Analyses including both alcohol and marijuana did not support an independent role for marijuana on alcohol effects on cerebellar gray matter trajectories. CONCLUSIONS: Alcohol use-related cerebellar growth trajectory differences from normal involved anterior lobules and vermis of youth who initiated substantial drinking. These regions are commonly affected in alcohol-dependent adults, raising the possibility that cerebellar structures affected with youthful drinking may be vulnerable to age-alcohol interactions in later adulthood.